Oratest: A new concept to test caries activity - S Saxena; Siddharth Pundir; Jain Aena (Wolters Kluwer Medknow Publications, 2013)
Caries activity tests are based on the concept of a specific odontogenic infection, the principle causative organism being streptococci mutans. Their predominance is attributed to its acidogenic and aciduric nature after a selective growth advantages over the other non- acid tolerant organisms. Many studies on caries activity are aimed at finding relevant microorganisms. Till date, the ideal method to evaluate in terms of sensitivity, specialization and reliability has not been found. Many of these caries activity tests require extensive work up time and additional equipment. Rosenberg et al. in 1989 developed Oratest, a simple, economical, non- invasive and less time-consuming test for estimating the oral microbial level. The test is simple and consists of rinsing the mouth with 10 ml of sterile milk, 3 ml of which is mixed with 0.12 ml of 0.1% methylene blue dye and observed for colour change. The present study sample consists of twenty five children with dental caries and twenty five controls, free of caries, gingivitis and other oral ailments. This study is being conducted in the department of Oral Pathology & Microbiology and is in the preliminary phase so further results are awaited.